Digitalisation Profile of the Elderly and ‘Grey Digital Violence’ - Hatice Oğuz Özgür (Yaşlı Sorunları Araştırma Dergisi)
Digital technologies which are widely used to fulfil certain needs in various areas of daily life have different and important functions for almost every age group. In this study, the use of digital tech-nologies by elderly individuals is explained in terms of which digital technologies they use fre-quently and for what purpose, and the acts of violence they experience during the use of these technologies are clarified. In order to make comparisons, the studies on the use of digital technolo-gies and experiences of digital violence by the elderly, especially as of 2011 were examined by using the data of the Household Information Technologies Usage Survey, which has been published regu-larly by the Turkish Statistical Institute (TURKSTAT) in recent years. It is seen that research on the use of digital technologies, especially the Internet, by the elderly has increased in recent years. According to these studies, the use of digital technologies by the elderly is increasing every year. This situation can be observed especially in the relevant statistics of the TURKSTAT. The purposes of the elderly to use digital technologies generally meet their needs such as communicating with family members, friends or relatives, socialising, obtaining information, making official transactions (making hospital appointments, paying bills, etc.). While realising these purposes, in recent years, they prefer tools such as smart mobile phones and computers that allow them to use the Internet. In addition to these findings, it is voiced in the related studies that the elderly also experience some undesirable actions in the digital environment with the increase in the intensity of their use of digital technologies. These negative experiences were described as ‘grey digital violence’ in the current study. The elderly are sometimes exposed to actions such as deception, fraud, insult and humiliation by those who use digital technologies with bad intentions. The studies reporting similar findings indicate that digital violence, which is characterised as today’s one of the important problems, threatens the digital security of not only young people but also the elderly.